2014
DOI: 10.1590/0102-311x00098213
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from liver cirrhosis in Espírito Santo State, Brazil

Abstract: To study mortality from liver cirrhosis in Espírito Santo State, Brazil, we reviewed death certificates (DC) from 2000-2010 and medical records of deceased patients with investigation of alcoholism and hepatitis B or C. From a total of 218,410 DC, 3,554 deaths from liver cirrhosis were retrieved. The annual mortality rate was 19.8/100,000 for men and 4.31/100,000 for women, without significant changes after correction for ICD-R98 and R99 and without a significant increase in the annual percentage change. In 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…In the present study, 12 out of 14 cases (31.58%) had history of alcohol liver disease whereas other 2 cases (25%) had history of jaundice with viral etiology. In study conducted by Goncalves et al [11] (2014), association of alcohol liver disease and cirrhosis was found to be 40.5%. In a study conducted by Nandakumar et al [12] (2003), frequency of virus induced cirrhosis was found to 25 % which is concordant with the present study (25%).…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, 12 out of 14 cases (31.58%) had history of alcohol liver disease whereas other 2 cases (25%) had history of jaundice with viral etiology. In study conducted by Goncalves et al [11] (2014), association of alcohol liver disease and cirrhosis was found to be 40.5%. In a study conducted by Nandakumar et al [12] (2003), frequency of virus induced cirrhosis was found to 25 % which is concordant with the present study (25%).…”
Section: Discussionmentioning
confidence: 90%
“…A taxa alta de etiologia indefinida (27%), no material estudado, está de acordo com estudos de Sifuentes3 e Gonçalves 12 que demonstraram 37,6% e 51%, respectivamente, de cirrose hepática de causa indeterminada, estando relacionada com populações de baixa renda que não possuem recursos suficientes para exames de investigação etiológica.…”
Section: Discussionunclassified
“…Liver cirrhosis is the final step of a process that arises as a result of numerous diseases, especially alcoholic liver disease and viral hepatitis; in addition it is considered a major cause of death worldwide [7][8][9][10] . In Brazil, studies focused on the etiology and mortality from liver cirrhosis is scarce [10][11][12] .…”
Section: The Casementioning
confidence: 99%
“…In Brazil, studies focused on the etiology and mortality from liver cirrhosis is scarce [10][11][12] . However, it is known that the prevalence of liver cirrhosis has increased in the Brazilian population, especially among the elderly.…”
Section: The Casementioning
confidence: 99%